Dilema Harta dalam Ikatan Cinta:Analisis Yuridis Sengketa Harta Bersama Menurut Hukum Perkawinan Indonesia - Muhlis Aditya; Astri Wulansari; Nugroho Nugroho (INDO PUBLISHING, 2026)
Marriage under Indonesian law not only forms a personal relationship between husband and wife but also gives rise to legal consequences regarding assets. One issue that frequently arises is disputes over joint property, particularly during divorce. This article aims to legally analyze the concept of joint property and the legal basis governing it in the Indonesian marital law system. The method used is a normative approach by examining laws and regulations, such as Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law, and the Civil Code. The analysis shows that joint property is property acquired during the marriage and, in principle, is divided fairly between husband and wife after divorce. However, in practice, this division often gives rise to disputes due to differing perceptions of contribution, lack of asset registration, and the absence of a prenuptial agreement. Therefore, a better understanding of the law and awareness of asset management from the beginning of the marriage are needed to minimize future conflict